2012
DOI: 10.1152/ajpregu.00501.2011
|View full text |Cite
|
Sign up to set email alerts
|

Functional differentiation of myoglobin isoforms in hypoxia-tolerant carp indicates tissue-specific protective roles

Abstract: Because of a recent whole genome duplication, the hypoxia-tolerant common carp and goldfish are the only vertebrates known to possess two myoglobin (Mb) paralogs. One of these, Mb1, occurs in oxidative muscle but also in several other tissues, including capillary endothelial cells, whereas the other, Mb2, is a unique isoform specific to brain neurons. To help understand the functional roles of these diverged isoforms in the tolerance to severe hypoxia in the carp, we have compared their O2 equilibria, carbon m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 48 publications
5
53
1
Order By: Relevance
“…) and under anaerobic conditions as previously described (Shiva et al, 2007;Pedersen et al, 2010;Helbo et al, 2012). The nitrite concentration of freshly made stock solutions (~20mmoll -1 ) was verified by the Griess reaction (Giustarini et al, 2008) prior to experiments.…”
Section: Nitrite Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…) and under anaerobic conditions as previously described (Shiva et al, 2007;Pedersen et al, 2010;Helbo et al, 2012). The nitrite concentration of freshly made stock solutions (~20mmoll -1 ) was verified by the Griess reaction (Giustarini et al, 2008) prior to experiments.…”
Section: Nitrite Reductionmentioning
confidence: 99%
“…Varying amounts of nitrite was added anaerobically to the Mb solution via a Hamilton gastight syringe (Bonaduz, Switzerland) and spectral changes were measured over time in the range 390-650nm using an HP 8543 UVvis diode array spectrophotometer. At the end of the reaction, deoxy Mb (peak at 555nm) was fully converted to the Fe-NO form (peaks at 545 and 572nm) as predicted by the reaction stoichiometry (Shiva et al, 2007;Pedersen et al, 2010;Helbo et al, 2012). Observed rates (k obs ; s -1 ) were obtained by fitting absorbance traces at 555nm to single exponential decay functions.…”
Section: Nitrite Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we assume that the potential beneficial effect of MB expression in cancer is independent from its primary respiratory functions, since the amount of MB protein expression would be too low to confer meaningful O 2 storage or buffering capacities (11). However, MB might play a scavenger role to support reduction of harmful ROS (5,22). In HNSCC, apart from mitochondrial processes, ROS are mainly produced by cigarette smoke; 86% of patients in our cohort have a documented smoking history.…”
Section: Discussionmentioning
confidence: 99%
“…Color is one of the most important factors affecting consumer preferences. The meat color of tuna is closely related with myoglobin (Mb) content and the red/ox state of the heme iron.Mb is a small globular protein whose biological function is basically to temporarily store oxygen in skeletal and cardiac muscles for facilitation of respiration (Livingston et al, 1983), though new functions of Mb have been recently reported, such as nitrogen oxide scavenging activity (Cossins and Berenbrink, 2008;Flögel et al, 2010;Helbo et al, 2012). Generally, Mb content changes dependent on animal species, muscle part, age, and diet of the animal.…”
mentioning
confidence: 99%